Sustainable aviation—hydrogen is the future - Talal, Yusaf; Louis, Fernandes; Abd Rahim, Abu Talib; Yazan S. M., Altarazi; Waleed, Alrefae; Kadirgama, Kumaran; Ramasamy, Devarajan; Jayasuriya, Aruna; Brown, Gordon; Rizalman, Mamat; Hayder, Al Dhahad; Benedict, F.; et al. (MDPI, 2022)
As the global search for new methods to combat global warming and climate change continues, renewable fuels and hydrogen have emerged as saviours for environmentally polluting industries such as aviation. Sustainable aviation is the goal of the aviation industry today. There is increasing interest in achieving carbon-neutral flight to combat global warming. Hydrogen has proven to be a suitable alternative fuel. It is abundant, clean, and produces no carbon emissions, but only water after use, which has the potential to cool the environment. This paper traces the historical growth and future of the aviation and aerospace industry. It examines how hydrogen can be used in the air and on the ground to lower the aviation industry’s impact on the environment. In addition, while aircraft are an essential part of the aviation industry, other support services add to the overall impact on the environment. Hydrogen can be used to fuel the energy needs of these services. However, for hydrogen technology to be accepted and implemented, other issues such as government policy, education, and employability must be addressed. Improvement in the performance and emissions of hydrogen as an alternative energy and fuel has grown in the last decade. However, other issues such as the storage and cost and the entire value chain require significant work for hydrogen to be implemented. The international community’s alternative renewable energy and hydrogen roadmaps can provide a long-term blueprint for developing the alternative energy industry. This will inform the private and public sectors so that the industry can adjust its plan accordingly.